2004
DOI: 10.1002/hep.1840400408
|View full text |Cite
|
Sign up to set email alerts
|

Influence of portal hypertension and its early decompression by TIPS placement on the outcome of variceal bleeding

Abstract: Increased portal pressure during variceal bleeding may have an influence on the treatment failure rate, as well as on short- and long-term survival. However, the usefulness of hepatic hemodynamic measurement during the acute episode has not been prospectively validated, and no information exists about the outcome of hemodynamically defined high-risk patients treated with early portal decompression. Hepatic venous pressure gradient (HVPG) measurement was made within the first 24 hours after admission of 116 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
289
0
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(315 citation statements)
references
References 36 publications
9
289
0
17
Order By: Relevance
“…More recently, a small study has suggested that early TIPS placement (within 24 hours of hemorrhage) is associated with a significant improvement in survival in "high-risk" patients (defined as those with an HVPG Ͼ20 mmHg) with acute variceal hemorrhage. 34 These results will require confirmation in a larger number of patients followed for a longer period before early TIPS can be recommended. The performance of both shunt surgery and TIPS are dependent on local expertise.…”
Section: Rescue Therapiesmentioning
confidence: 94%
See 1 more Smart Citation
“…More recently, a small study has suggested that early TIPS placement (within 24 hours of hemorrhage) is associated with a significant improvement in survival in "high-risk" patients (defined as those with an HVPG Ͼ20 mmHg) with acute variceal hemorrhage. 34 These results will require confirmation in a larger number of patients followed for a longer period before early TIPS can be recommended. The performance of both shunt surgery and TIPS are dependent on local expertise.…”
Section: Rescue Therapiesmentioning
confidence: 94%
“…[30][31][32] Patients with an HVPG Ͼ20 mmHg (measured within 24 hours of variceal hemorrhage) have been identified as being at a higher risk for early rebleeding (recurrent bleeding within the first week of admission) or failure to control bleeding (83% vs. 29%) and a higher 1-year mortality (64% vs. 20%) compared to those with lower pressure. 33,34 Late rebleeding occurs in approximately 60% of untreated patients, mostly within 1-2 years of the index hemorrhage. 35,36 Variceal wall tension is probably the main factor that determines variceal rupture.…”
Section: Natural History Of Varicesmentioning
confidence: 99%
“…In the Baveno conference, it was considered that a second attempt at endoscopic therapy was one possibility and one could perform TIPS after failure of the second endoscopic therapy [1]. A small study suggests that early TIPS placement (within 24 h of hemorrhage) is associated with a significant improvement in survival in patients with HVPG greater than 20 mmHg [31]. Therefore, HVPG can provide useful information that allows for risk stratification and more aggressive treatment in high-risk patients.…”
Section: Role Of Rescue Therapies In Avbmentioning
confidence: 99%
“…This is the rationale for preemptive or early TIPS [8]. Indeed, two RCT [9,10] and two observational studies confirm the efficacy of early TIPS (within the first 72 h after admission) in such high-risk patients. Indeed, experts attending the Baveno VI consensus conference recommended the use of early TIPS in patients with Child-Pugh B cirrhosis and active bleeding despite vasoactive drug therapy and in all patients with Child-Pugh C cirrhosis (< 14 points) [3].…”
mentioning
confidence: 96%